2014
DOI: 10.1002/ps.3772
|View full text |Cite
|
Sign up to set email alerts
|

Do plant trichomes cause more harm than good to predatory insects?

Abstract: Plants use trichomes as a morphological defense against attacks from herbivores. The literature was reviewed to test the hypothesis that trichome-bearing (pubescent) plants do not cause more harm than good to predators. Forty seven records on interactions between plant trichomes and predatory insects were found. Overall, the records reveal that trichomes have more harmful than beneficial effects on predators. Fortunately, most harmful effects are sublethal; they usually affect movement, development, ovipositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 90 publications
(225 reference statements)
1
73
0
1
Order By: Relevance
“…A generalized schematic of the positive (+), neutral (o), or negative (--) interactions that could arise between these factors is presented in Figure 1. Prior research conducted primarily in the laboratory and in open field settings suggests that host plant defenses could have negative or neutral effects on aphids as well as ladybirds [41]. Also, aphid density has a positive effect on ladybirds [21,22], but the effect can become negative if prey becomes scarce, resulting in starvation or cannibalism amongst immature ladybirds.…”
Section: Introductionmentioning
confidence: 99%
“…A generalized schematic of the positive (+), neutral (o), or negative (--) interactions that could arise between these factors is presented in Figure 1. Prior research conducted primarily in the laboratory and in open field settings suggests that host plant defenses could have negative or neutral effects on aphids as well as ladybirds [41]. Also, aphid density has a positive effect on ladybirds [21,22], but the effect can become negative if prey becomes scarce, resulting in starvation or cannibalism amongst immature ladybirds.…”
Section: Introductionmentioning
confidence: 99%
“…Roles in the drought and heat stresses (Ehleringer, 1982;Grammatikopoulos and Manetas, 1994;Espigares and Peco, 1995;Pérez-Estrada et al, 2000) and heavy metal detoxification and deposition (Salt et al, 1995;Pérez-Estrada et al, 2000;Servin et al, 2012;Jr and Kupper, 2014) also have been described. Additionally, different forms of trichomes have been linked to increased plant resistance against herbivores across different species of plants (for review, see Riddick and Simmons, 2014).…”
mentioning
confidence: 99%
“…When we conducted a second experiment comparing survival of O. insidiosus on A c c e p t e d M a n u s c r i p t glandular and non-glandular cuphea, more dead individuals were removed from locations on the glandular plants than on the non-glandular plants, indicating glandular trichomes can play a significant role in O. insidiosus mortality. Previous research has shown that predators can become entangled by the sticky exudate produced by the heads of glandular trichomes, impeding their search behavior, reducing oviposition rates, and potentially resulting in death from starvation or from toxins in the exudate (Lovinger, Liewehr, & Lamp, 2000;Gassmann & Hare, 2005;Smith, 2005;Riddick & Simmons, 2014). Although sublethal effects from glandular trichomes are common, ours is one of the comparatively few studies to show increased mortality in the presence of glandular trichomes (Riddick & Simmons, 2014).…”
Section: Discussionmentioning
confidence: 86%